O mal e a catástrofe em Eles eram muitos cavalos, de Luiz Ruffato - Sikora, Scheila Aparecida Ribeiro (2014)
The aim of this work is to study the representation of evil and its possible rolesin the failure of four characters in four narratives of Eles eram muitos cavalos, by Luiz Ruffato, a book published in 2001. By using bibliographical references in this matter, we discuss the definitions of primitivity, civilization (Freud, 2011; 2013) and progress (Adorno and Horkheimer, 1947). Besides, we discuss the concept of evil (Freud, 2011; Bataille, 1989; Arendt, 2013; Agamben, 2008, 2013; Baudrillard, 1991) our study consists on identifying evil and its reverberations throughout the narratives, in the chosen characters and in literature as a whole. We also discuss some aspects which can be seen as result of evil, such as primitive groups, civilization, progress and catastrophe.